The effects of verbal instruction on affective and expectancy learning - Lipp, Ottmar; Mallan, K.; Libera, M.; Tan, M. (Elsevier, 2010)
The current research assessed the effects of verbal instruction on affective and expectancy learning during repeated contingency reversals (Experiment 1) and during extinction (Experiment 2) in a picture-picture paradigm. Affective and expectancy learning displayed contingency reversal and extinction, but changes were slower for affective learning. Instructions facilitated reversal and extinction of expectancy learning but did not impact on affective learning. These findings suggest a differential susceptibility of affective and expectancy learning to verbal instruction and question previous reports that verbal instructions can accelerate the extinction of non-prepared fear learning in humans. © 2009 Elsevier Ltd. All rights reserved.